Sex differences in the characteristics of stimulant offenders with a history of substance use disorder treatment - Ayumi Kondo; Takuya Shimane; Masaru Takahashi; Michiko Kobayashi; Marie Otomo; Yoshiko Takeshita; Toshihiko Matsumoto (Wiley, 2023)
Abstract We analyzed the results of a nationwide questionnaire administered to 699 stimulant offenders and examined sex differences in the association between various psychosocial problems and treatment history for substance use disorder. Based on their attributes, we predominantly evaluated the treatment and support provided to women with substance use disorder. The rates of childhood (before the age of 18) traumatic experiences (physical, psychological, and sexual abuse and neglect) and lifetime intimate partner violence were significantly higher in women than in men. The history of treatment for substance use disorder was also significantly higher in women than in men, at 15.8% for men and 42.4% for women [χ2(1) = 41.223, p < 0.001]. Logistic regression analysis was performed using the treatment history of substance use disorder as the dependent variable. The results showed that treatment history was significantly associated with the total drug abuse screening test‐20 score and suicidal ideation in men and with survivors of child abuse and eating disorders in women. A comprehensive assessment is required for several issues, such as child abuse, domestic violence, trauma symptoms, eating disorders, and drug problems. Moreover, an integrated treatment for substance use disorder, trauma, and eating disorders is required for female stimulant offenders.